Criminology in the face of flows: reflections on contemporary policing and security. Issue 3 (3rd July 2017) - Amicelle, Anthony; Côté-Boucher, Karine; Dupont, Benoît; Mulone, Massimiliano; Shearing, Clifford; Tanner, Samuel
ABSTRACT: Much has been written about the governance of crime – indeed, this is the thread that has unified criminology. Yet, property crimes and attacks against individuals – traditionally at the core of the discipline – are plummeting in many societies. Meanwhile, harms and harm management emerge outside the narrowness of criminal justice definitions. Despite this, little criminological attention has been paid to the fact that the security of flows increasingly embodies concerns that are at the heart of contemporary policing practices. This introduction to this special issue takes stock of these changes and argues that to stay current and relevant, criminology must pay closer attention to these changing landscapes of harms and policing.